2011
DOI: 10.1155/2011/640535
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Evoked Potentials in Children of Diabetic Mothers

Abstract: Type 1 diabetic mothers' infants show a delay of visual evoked potential (VEP) significantly related to some parameters of poor metabolic control during pregnancy. In the present paper we analyzed the characteristics of VEPs and somatosensory evoked potentials (SEPs) recorded in 16 three-year-old type 1 diabetic mothers' children (DMC). Compared with controls (23 nondiabetic mothers' healthy matched children), DMC showed significantly delayed mean latency of VEP (P2) and SEP (P22). In 3 cases (19%), we found p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In CDMs, visual-evoked potentials and somatosensory-evoked potentials vary as a function of metabolic control during pregnancy with CDMs exhibiting delays in cortical evoked responses relative to children of non-diabetic mothers (31). Similar results have been previously obtained in our sample using electrophysiological measures.…”
Section: Discussionmentioning
confidence: 99%
“…In CDMs, visual-evoked potentials and somatosensory-evoked potentials vary as a function of metabolic control during pregnancy with CDMs exhibiting delays in cortical evoked responses relative to children of non-diabetic mothers (31). Similar results have been previously obtained in our sample using electrophysiological measures.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced inner/outer macular thickness and total macular volume have been reported in children of diabetic mothers (8). Brinciotti et al (9) showed that type 1 DM mothers’ offspring had a significant delay of cortical evoked responses to visual stimulation compared with controls at both infancy and 3 years of age. Ricci et al (10) examined hypoplasia of iris stroma in 90% of infants with diabetic mothers and detected altered pupil dynamics in 85% of these infants in the first 3 days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have determined the long‐term effects of maternal diabetes on the offspring of mothers with diabetes. These studies detected delayed cortical evoked responses in the visual and somatosensory systems of 3‐year‐old offspring of type 1 diabetic mothers and lower cognitive test scores in adult offspring of women with diet‐treated gestational diabetes (Brinciotti et al, 2011; Clausen et al, 2013).…”
Section: Methodsmentioning
confidence: 99%